Emergency Airway Management During Awake Craniotomy: Comparison of 5 Techniques in a Cadaveric Model. Issue 1 (13th January 2022) - Gruenbaum, Shaun E.; Bilotta, Federico; Bertasi, Tais G.O.; Bertasi, Raphael A.O.; Clifton, William E.; Gruenbaum, Benjamin F.; De Biase, Gaetano; Garcia, Diogo M.; Bojaxhi, Elird; Torp, Klaus D.; Quinones-Hinojosa, Alfredo
Abstract : Background: During awake craniotomy, securing the patient's airway might be necessary electively or emergently. The objective of this study was to compare the feasibility of airway management using a laryngeal mask airway (LMA) and 4 alternative airway management techniques in an awake craniotomy simulation. Methods: After completing a questionnaire, 9 anesthesia providers attempted airway management in a cadaver positioned to simulate awake craniotomy conditions. Following the simulation, participants rated and ranked the devices in their order of preference. Results: Only 3 approaches resulted in the successful securement of an airway device for 100% of participants: LMA (median; interquartile range time to secure the airway 6 s, 5 to 10 s), fiberoptic bronchoscopy through an LMA (41 s; 23 to 51 s), and video laryngoscopy (49 s; 43 to 127 s). In contrast, the oral and nasal fiberoptic approaches demonstrated only 44.4% (154.5 s; 134.25 to 182 s) and 55.6% (75 s; 50 to 117 s) success rates, respectively. The LMA was the fastest and most reliable primary method to secure the airway ( P =0.001). After the simulation, 100% of participants reported that an LMA would be their first choice for emergency airway management, followed by fiberoptic intubation through the LMA (7 of 9 participants) if the LMA failed to properly seat. Conclusions: We demonstrated that an LMA was the fastest and most reliable primary method to secure an airway in a laterally positioned cadaver with 3-pin skull fixation. Fiberoptic and video laryngoscope airway equipment should be readily available during awake craniotomy procedures, and an attempt to visualize the vocal cords through the LMA should be attempted before removing it for alternative techniques.